High Serum Vitamin D Concentrations, Induced via Diet, Trigger Immune and Intestinal Microbiota Alterations Leading to Type 1 Diabetes Protection in NOD Mice - Martens, Pieter-Jan; Centelles-Lodeiro, Javier; Ellis, Darcy; Cook, Dana Paulina; Sassi, Gabriele; Verlinden, Lieve; Verstuyf, Annemieke; Raes, Jeroen; Mathieu, Chantal; Gysemans, Conny (Frontiers in Immunology, 2022)
The hormonally-active form of vitamin D, 1,25-dihydroxyvitamin D3, can modulate both innate and adaptive immunity, through binding to the nuclear vitamin D receptor expressed in most immune cells. A high dose of regular vitamin D protected non-obese diabetic (NOD) mice against type 1 diabetes (T1D), when initiated at birth and given lifelong. However, considerable controversy exists on the level of circulating vitamin D (25-hydroxyvitamin D3, 25(OH)D3) needed to modulate the immune system in autoimmune-prone subjects and protect against T1D onset. Here, we evaluated the impact of two doses of dietary vitamin D supplementation (400 and 800 IU/day), given to female NOD mice from 3 until 25 weeks of age, on disease development, peripheral and gut immune system, gut epithelial barrier function, and gut bacterial taxonomy. Whereas serum 25(OH)D3 concentrations were 2.6- (400 IU/day) and 3.9-fold (800 IU/day) higher with dietary vitamin D supplementation compared to normal chow (NC), only the 800 IU/day vitamin D-supplemented diet delayed and reduced T1D incidence compared to NC. Flow cytometry analyses revealed an increased frequency of FoxP3+ Treg cells in the spleen of mice receiving the 800 IU/day vitamin D-supplemented diet. This vitamin D-induced increase in FoxP3+ Treg cells, also expressing the ecto-5’-nucleotidase CD73, only persisted in the spleen of mice at 25 weeks of age. At this time point, the frequency of IL-10-secreting CD4+ T cells was also increased in all studied immune organs. High-dose vitamin D supplementation was unable to correct gut leakiness nor did it significantly modify the increased gut microbial diversity and richness over time observed in NOD mice receiving NC. Intriguingly, the rise in alpha-diversity during maturation occurred especially in mice not progressing to hyperglycaemia. Principal coordinates analysis identified that both diet and disease status significantly influenced the inter-individual microbiota variation at the genus level. The abundance of the genera Ruminoclostridium_9 and Marvinbryantia gradually increased or decreased, respectively in faecal samples of mice on the 800 IU/day vitamin D-supplemented diet compared to mice on the 400 IU/day vitamin D-supplemented diet or NC, irrespective of disease outcome. In summary, dietary vitamin D reduced T1D incidence in female NOD mice at a dose of 800, but not of 400, IU/day, and was accompanied by an expansion of Treg cells in various lymphoid organs and an altered intestinal microbiota signature.